The Chlamydia pneumoniae Tarp Ortholog CPn0572 Stabilizes Host F-Actin by Displacement of Cofilin - Zrieq, Rafat; Braun, Corinna; Hegemann, Johannes H. (Frontiers in Cellular and Infection Microbiology, 2017)
Pathogenic Chlamydia species force entry into human cells via specific adhesin-receptor interactions and subsequently secrete effector proteins into the host cytoplasm, which in turn modulate host-cell processes to promote infection. One such effector, the C. trachomatis Tarp factor, nucleates actin polymerization in vitro. Here we show that its C. pneumoniae ortholog, CPn0572, associates with actin patches upon bacterial invasion. GFP-CPn0572 ectopically expressed in yeast and human cells co-localizes with actin patches and distinctly aberrantly thickened and extended actin cables. A 59-aa DUF 1547 (DUF) domain, which overlaps with the minimal actin-binding and protein oligomerization fragment required for actin nucleation in other Tarp orthologs, is responsible for the aberrant actin phenotype in yeast. Interestingly, GFP-CPn0572 in human cells associated with and led to the formation of non-actin microfilaments. This phenotype is strongly enhanced in human cells expressing the GFP-tagged DUF deletion variant (GFP-ΔDUF). Finally ectopic CPn0572 expression in yeast and in-vitro actin filament binding assays, demonstrated that CPn0572 stabilizes pre-assembled F-actin by displacing and/or inhibiting binding of the actin-severing protein cofilin. Remarkably, the DUF domain suffices to displace cofilin from F actin. Thus, in addition to its actin-nucleating activities, the C. pneumoniae CPn0572 also stabilizes preformed host actin filaments.